1996
DOI: 10.1063/1.881509
|View full text |Cite
|
Sign up to set email alerts
|

Helium in Aerogel

Abstract: An important theme that threads through many areas of current interest in condensed matter physics is the effect of randomness and disorder. Prior to the 1960s, disorder and impurities were often viewed as unavoidable nuisances that masked the true behavior of ideal systems. We have since learned that disorder itself can bring forth fascinating and often unexpected new phenomena in condensed phases of matter. (See the December 1988 special issue of PHYSICS TODAY, dedicated to disordered solids.)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
88
1

Year Published

1997
1997
2010
2010

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(90 citation statements)
references
References 22 publications
1
88
1
Order By: Relevance
“…There is increasing interest in the dynamical properties of systems that are characterized by prominent quantum statistical effects, such as the spectroscopy of impurity atoms or molecules embedded in superfluid 4 He nanodroplets (38)(39)(40), the manifestation of superfluidity and BEC in confined geometries such as on surfaces and in porous media (41), and the recently reported observation of ''supersolidity'' (42). The combined quantum-semiclassical methodology used in the calculations presented in this article will help deepen the microscopic understanding of the intriguing dynamical behaviors of such systems.…”
Section: Resultsmentioning
confidence: 99%
“…There is increasing interest in the dynamical properties of systems that are characterized by prominent quantum statistical effects, such as the spectroscopy of impurity atoms or molecules embedded in superfluid 4 He nanodroplets (38)(39)(40), the manifestation of superfluidity and BEC in confined geometries such as on surfaces and in porous media (41), and the recently reported observation of ''supersolidity'' (42). The combined quantum-semiclassical methodology used in the calculations presented in this article will help deepen the microscopic understanding of the intriguing dynamical behaviors of such systems.…”
Section: Resultsmentioning
confidence: 99%
“…For 3 He- 4 He mixtures, the presence of 2% or even 0.5% silica (i.e. aerogels with porosity of 98% or 99.5%) has dramatic effects 5,6,7 on the entire phase diagram, causing the phase separation curve to detach from the lambda line and stabilizing a region of dilute 4 He superfluid inaccessible in bulk mixtures.…”
Section: Introductionmentioning
confidence: 99%
“…The experimental efforts have concentrated on idealized model systems in the hopes of isolating the essential features of quenched random disorder. They include the still enigmatic superfluid transition of 4 He in aerogels and porous glasses, the superfluid transition and phase separation of 4 He- 3 He mixtures in silica aerogels [1] and doped magnet systems [2]. Relatively recent efforts with liquid crystal (LC) -silica composites [3,4,5,6,7,8,9] have demonstrated that these are especially interesting model systems.…”
Section: Introductionmentioning
confidence: 99%